Exploring social media addiction among Malaysian University students / Nurul Fatin Najihah Zulkifli and Muhammad Zaiamri Zainal Abidin - Zulkifli, Nurul Fatin Najihah; Zainal Abidin, Muhammad Zaiamri (Faculty of Communication and Media Studies (FCMS), 2023)
Social media platforms have become integral to the lives of university students in Malaysia, presenting both benefits and risks. The pervasive use of social media has revolutionized communication and information-sharing among university students in Malaysia. However, excessive engagement with social media platforms can lead to addictive behaviours, negatively impacting students’ academic performance, mental health, and social relationships. This qualitative research article aims to explore the phenomenon of social media addiction among university students in Malaysia, examining the underlying factors contributing to addictive behaviours. Through in-depth interviews and thematic analysis, this study identifies three key themes related to social media addiction and provides insights into the experiences, perceptions, and coping mechanisms employed by university students which include the relationship between social media and hedonic satisfaction, the relationship between social media and functional satisfaction, and the relationship between social media and social satisfaction. The findings contribute to the existing body of knowledge on social media addiction and inform interventions to promote healthy social media use among this population.